2020
DOI: 10.36306/konjes.705209
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Austenitizing Temperature on the Austempering Behavior of EN-GJS- 600-3 Spheroidal Graphite Cast Iron

Abstract: Bu çalışmada östenitleme sıcaklığının EN-GJS-600-3 (GGG-60) küresel grafitli dökme demirin östemperlenme davranışına etkisi araştırılmıştır. Y bloklarına dökülen % 0,5 Cu alaşımlı EN-GJS-600-3 küresel grafitli dökme demirden çıkarılan numuneler kullanılarak iki farklı östenitleme sıcaklığı (850 ve 950°C) ve iki farklı östemperleme sıcaklığının (290 ve 320°C) dört ayrı kombinasyonunda östemperleme deneyleri yapılmıştır. Östemperleme deneyleri sonrası numunelerin sertlik ölçümleri, çekme testleri ve iç yapı ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…At the end of the examination, they concluded that the processes performed differed considerably in the microstructure and the mechanical properties were improved. [10].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the examination, they concluded that the processes performed differed considerably in the microstructure and the mechanical properties were improved. [10].…”
Section: Introductionmentioning
confidence: 99%